Impacts of Magnetic Iron Oxide Nanoparticles in Terrestrial and Aquatic Environments - Grillo, Renato; Fraceto, Leonardo F. [UNESP] (Wiley, 2021)
Use of magnetic iron oxide nanoparticles (IONPs) has found utility across many domains to include biotechnology and medicine, materials science, and environmental remediation. This is due in large part to their small size, surface chemistry, and magnetic properties. Although the properties, synthesis, and diverse industrial and commercial uses of IONPs are well described in the literature, little is known about their potential adverse environmental impacts once released to aquatic and terrestrial ecosystems, and of course possible effects on human health. This chapter comprehensively discusses the emergent commercial applications of IONPs, particularly in clinical medicine, imaging and diagnostic applications, and other areas to include food engineering, and environmental mitigation to include removal of contaminants like heavy metals, dyes, and pesticides, among others. Given their broad utility, this chapter critically discusses the known environmental fate, behavior, and toxicity of IONPs with a particular emphasis on aquatic and terrestrial systems. In the final section of this chapter, the known data and knowledge gaps are surveyed, particularly in regard to the speciation of IONPs nano-particles, trophic transfer and their potential for bioaccumulation, and biomagnification. In addition, the interactive effects of IONPs with diverse environmental species, which is influenced by a variety of environmental conditions to include pH and ionic strength, and temperature is considered. This chapter clearly identifies an urgent need for further environmental research and a critical need to characterize the environmental safety and aquatic/terrestrial toxicity of these novel nanomaterials.
Keywords: aquatic systems; environmental impact; iron oxide nanoparticles; soil